Investigation Towards the Needs of Affective Design Principles of Mathematics Mobile Application for Low Vision Learners - Mutalib, Nur Amirah Abdul; Salam, Sobihatun Nur Abdul; Aziz, Nurulnadwan (CENTRAL ASIA AND THE CAUCASUS, 2021)
The aim of the study is to investigate the development of affective design principle of mathematics mobile application needs for low vision learners. Semi- structured interviews have been performed for the investigation as a method. As a result, the needs for affective design principles of mobile application in learning mathematics for low vision learners have been confirmed. In conclusion, it is clearly revealed that the existing mobile application specifically design for affective design principles is still scarce and there is a significant needs towards the development of affective design principle of mathematics mobile application for low vision learners.